(untitled) (The Pretoria Student Law Review, 2021)
Documentary letters of credit are important tools in relation to international trade. The parties who make use of these instruments usually come from different countries and usually have different views on trade and customs. The parties generally do not know each other personally and have opposite interests in relation to the contract of sale. There is a sense of distrust towards each other, as both parties have serious concerns as to the other’s performance in terms of the contract. While the purchaser has a fear of receiving goods of an incorrect quantity or quality, or not receiving goods at all, the seller fears non-payment, or that the buyer refuses to accept the goods on a mere technicality. Coupled with the abovementioned is the fact that legal recourse will be expensive and may be complex taking jurisdiction into consideration. A documentary letter of credit eases some of these fears due to the unique doctrines which form the foundation of this instrument, and these will be discussed at length. The most frequently encountered exception to documentary letters of credit not being fulfilled is that of fraud, which will also be discussed at length.